Association of Serum Angiopoietin-Like Protein 8 With Albuminuria in Type 2 Diabetic Patients: Results From the GDMD Study in China - Yang, Liuxue; Song, Jianfei; Zhang, Xiaoxi; Xiao, Liuping; Hu, Xueping; Pan, Haidong; Qin, Linyuan; Liu, Hongbo; Ge, Bo; Zheng, Tianpeng (Frontiers in Endocrinology, 2018)
Background: Hyperglycemia, insulin resistance and hypertriglyceridesmia are risk factors for albuminuria in type 2 diabetes. Angiopoietin-like Protein 8(ANGPTL8) is a newly identified liver-derived hormone related to these risk factors. Hence, we aimed to explore the relationship between ANGPTL8 and albuminuria in type 2 diabetes. Methods: Serum ANGPTL8 levels were determined in groups of control (n = 50) and type 2 diabetic patients with normoalbuminuria (A1, n = 100), microalbuminuria (A2, n = 45), and macroalbuminuria (A3, n = 33). Results: Serum levels of ANGPTL8 and triglycerides were significantly increased in type 2 diabetic patients with albuminuria as compared with controls (P < 0.001). ANGPTL8 levels were positively correlated with triglycerides, duration of diabetes, and urine albumin-to-creatinine ratio (ACR) and negatively correlated with estimated glomerular filtration rate in type 2 diabetic patients with A2 and A3 (all P < 0.05). Logistic regression analysis indicated that ANGPTL8 had higher odds of having A2 (OR= 2.52, 95 % CI 1.16–5.48, P = 0.019) and A3 (OR = 4.89, 95 % CI 2.10–11.39, P<0.001) in type 2 diabetes. Mediation analysis indicated that triglycerides might act as a partial mediator in the relationship between ANGPTL8 and ACR. Conclusions: Triglycerides might partially mediate the correlation between ANGPTL8 and ACR. Our data provide the evidence for a strong link between ANGPTL8 and albuminuria, indicating that ANGPTL8 may be a new biomarker for diabetic kidney disease in type 2 diabetes.